Income inequality and level of corruption in post-communist European countries between 1995 and 2014. Issue 2 (June 2019) - Bašná, Kristýna
Abstract: This paper analyses the relationships between income inequality and corruption in Europe and looks specifically at post-communist European countries. The scientific community agrees that there is important relationship between income inequality and corruption and many authors believe that low income inequality is connected to low corruption. According to empirical papers, this is true not only on the European scale, but also on a global scale. In this paper, I test this claim by conducting a multilevel analysis on 39 European countries in the period of 1995–2014. This model ascertains that there are immense differences between post-communist countries and the rest of European countries. The effects of income inequality on the level of corruption are discussed.